Rancang Bangun Sistem Pemantau Suhu dan Kelembaban Pada Gudang Penyimpanan PR. Alfi Putra Trenggalek dengan LoRa, Metode CSMA/CA, dan Aplikasi Telegram - Adji Kuncoro Bhangun; Mochammad Hannats Hanafi Ichsan; Eko Setiawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
The tobacco industry is one of many industries that has a big influence on the economy. In the tobacco storage process, it is necessary to pay attention on temperature and humidity conditions at the tobacco warehouse. But the monitoring process of these conditions are still manual, and this prove to be difficult to do if the factory staffs are outside the industrial zone. Therefore, the temperature and humidity monitoring system with WSN (Wireless Sensor Network) technology become a solution to these problems. System is comprised of 3 (three) slave nodes which perform sensing of temperature and humidity, and 1 (one) master node that collects and processes data received from each node, and sends data to users via Telegram app. From the test results, system is capable to sense with the error on temperature and humidity sensing on node 1 0,53% and 1,46%, node 2 0,43% and 6,98%, and node 3 0,14% and 1,87%, also the system is capable to send its data with an RSSI value at node 1 -59.82 dB, node 2 -52.52 dB, and node 3 -70.42 dB. The system is capable to send data using CSMA/CA method with RTT during the RTS/CTS at node 1 is 84 milliseconds, node 2 is 59 milliseconds, and node 3 is 60 milliseconds. Meanwhile, RTT when sending data at node 1 is 67 milliseconds, node 2 is 59 milliseconds, and node 3 is 60 milliseconds, and data collision probability can be minimized to 4%. Finally, the system is capable to send notifications when the temperature and humidity conditions exceed the optimal limit through the Telegram app and able to reply the commands from users with an average response time of 12.6 seconds.